O alcoolismo entre os mecânicos de manutenção de veículos: um estudo de caso em Belo Horizonte - MG - Alessandro Vinicius de Paula (2008)
The objective of this investigation is to verify the possible relations between the exercise of mechanic activity in vehicle maintenance for the Department of Vehicle Maintenance of a public company responsible for urban cleaning in Belo Horizonte (MG), Brazil, and possible development and/or aggravation of alcoholism among Department workers. We searched to explain, above all, the mediators between mechanic activities and the development of alcoholism. The studys data collection was divided in two stages: field observations and deep interviews for individual case studies. Two case studies were developed in order to (re)build the relation between alcohol use and life and work conditions of the participants. The study brought some elements that reveal the difficulties suffered by the mechanics of vehicle maintenance at work, allowing the comprehension of alcoholism in the group studied and its context.